FENOMENA HARBOLNAS (HARI BELANJA ONLINE NASIONAL) MELALUI HARGA, PRODUK, KEMUDAHAN DAN KEAMANAN BERTRANSAKSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN SECARA ONLINE DENGAN KEPERCAYAAN SEBAGAI VARIABEL MODERATING DI KOMPLEK JOHOR INDAH PERMAI II MEDAN - Wisnu Rayhan Adhitya (Jurnal Prodi Fakultas Ekonomi-UISU, 2019)
Harbolnas (National Online Shopping Day) is a day of celebration to encourage and educate the public about the convenience of online shopping. Online buying and selling sites have started to promote it in television media, and are competing to become the best online buying and selling forum site. The number of business people who market their products will give people the choice to buy it more easily, practically and economically by accessing the site. The purpose of this research is to find out and analyze the variables that most influence consumer purchasing decisions online(1), To find out and analyze trust variables that partially affect consumer purchasing decisions online(2), To find out and analyze trust that moderates all independent variables on consumer purchasing decisions online(3). The data collecting method is interview, questioner, and documentation. The data analyze method is structural equation modeling (SEM) with partial least square (PLS).Keywords : National Online Shopping Day, Price, Product, Easinees in transaction, Safety in Transaction, Credibility and Decision to shop online